Ultrafast nonadiabatic cascade and subsequent photofragmentation of extreme ultraviolet excited caffeine molecule - Marciniak, Alexandre; Kuleff, Alexander I. (The journal of physical chemistry letters, 2018)
Ultrafast XUV chemistry is offering new opportunities to decipher the complex dynamics taking place in highly excited molecular states and thus better understand fundamental natural phenomena as molecule formation in interstellar media. We used ultrashort XUV light pulses to perform XUV pump-IR probe experiments in caffeine as a model of prebiotic molecule. We observed a 40 fs decay of excited cationic states. Guided by quantum calculations, this time scale is interpreted in terms of a nonadiabatic cascade through a large number of highly correlated states. This shows that the correlation driven nonadiabatic relaxation seems to be a general process for highly excited states, which might impact our understanding of molecular processing in interstellar media.
Gesehen am 11.10.2019